Management of gastrointestinal carcinoid tumours - 10 years experience at a district general hospital - Dronamraju, Shridhar S. (Pioneer Bioscience Publishing Company, 2012)
BACKGROUND: There is paucity of guidelines regarding management of gastrointestinal carcinoid tumours in district hospitals. METHODS: This study was undertaken at a district hospital to analyse the management pathway of gastrointestinal carcinoid tumours. RESULTS: Over a period of 10 years there were 35 patients, with an estimated annual incidence of 2.5 per 100,000 population. After a median follow up of 24 months, 22 (63%) patients were alive and disease free. Only 56% patients were referred to the regional neuro-endocrine multidisciplinary team. CONCLUSIONS: Management of patients with carcinoid tumours in district hospitals needs streamling with increased utilisation of regional neuroendocrine multidisciplinary teams.